Social skills and general self-efficacy in students of the VII cycle of regular public basic education - Cunza Aranzábal, Denis Frank (2024)
This study was conducted to determine the relationship between social skills and general self-efficacy in adolescent students of the VII cycle of regular state basic education, from Cerro de Pasco. The research was non-experimental, cross-sectional and correlational in scope, with a sample of 353 students between 14 and 17 years old, belonging to the VII cycle of two secondary national educational institutions in Cerro de Pasco. The Social Skills Scale (EHS) and the General Self-Efficacy Scale (GSS) were used. The results indicate that social skills are positively and significantly related to general self-efficacy (r = 0.264, p < 0.01). Therefore, it can be said that the better the development of social skills in the adolescent, the greater the general self-efficacy.